Effect of Trichoderma Spp. as a Bio-control Agent on Cereal Crop Plants - Yadav, S G (Plantae Scientia, 2020)
Trichoderma is a Deuteromycetous fungus with hyphae long, creeping, conidiophores erect, philiadic, having conidial heads. Trichoderma species produces a chemical, trichodermin; it is the sesquiteroenoid acting as a bio-control agent on the principal of myco-parasitism, antibiosis and competition to control soil borne plant pathogens. The phytotoxic effect was screened by treating cereal crop seeds with culture filtrate of Trichoderma species, the effect of culture filtrate was measured in terms of seed germination percentage and results were compared with control one. The obtained results shows percentage of germination in treated seeds was more than the control. The culture filtrate of Trichoderma harzianum showed superior effects (95-97%) than that of Trichoderma viridae (90-95%) and Trichoderma virens (86-92%) on the seed germination of selected cereal crop seeds